ANALISIS VEGETASI MANROVE MENGGUNAKAN (NDVI) PADA EKOSISTEM MANGGROVE DI KECAMATAN BALINGGI KABUPATEN PARIGI MOUTONG - Setiawan, Andri; Akhbar, Akhbar; Arianingsih, Ida (ForestSains, 2018)
This study aims to determine the area-level greenness of mangrove ecosystems in Balinggi Sub-district, Parigi Moutong Regency, Central Sulawesi, by using Landsat 8 image data. It is expected to provide information about the normalized difference Vegetation Index (NDVI) of each site that has been analyzed using GIS. The observation was conducted in June â€“August 2017. The research method used in this study was by assessing the mangrove density or the level of greenness using the vegetation index method through the NDVI formula, which is effective as an initial division of vegetation areas. The NDVI can be an indicator to measure green leaf biomass and leaf area index for the classification of vegetation. Based on the results of Landsat 8 image data of 2016, the total area of mangrove forest vegetation in Balinggi was 163.30 ha and can be classified into three classes of vegetation density, namely: low (26.46 ha), moderate (55.54 ha) and high (80.08 ha). Furthermore, based on the table of Landsat image classification, the low density class has â€œvery goodâ€ land use accuracy with a value of 100% while the high and moderate density classes have â€œgoodâ€ land use accuracy of 75% and 67%, respectively.